2022
DOI: 10.3390/cancers14061394
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Histological Distribution Analysis Identify Mast Cell Heterogeneity in Non-Small Cell Lung Cancer

Abstract: Mast cells (MCs) are multifaceted innate immune cells often present in the tumor microenvironment (TME). However, MCs have been only barely characterized in studies focusing on global immune infiltrate phenotyping. Consequently, their role in cancer is still poorly understood. Furthermore, their prognosis value is confusing since MCs have been associated with good and bad (or both) prognosis depending on the cancer type. In this pilot study performed on a surgical cohort of 48 patients with Non-Small Cell Lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
(59 reference statements)
0
15
0
Order By: Relevance
“…This, in turn, effectively activated T cells. The study also indicated that lung cancer patients with high mast cell infiltration in the tumor microenvironment exhibited better overall and disease-free survival ( 69 ). In addition, it has been reported that MHC protein is one of the key molecules in presenting antigens and activating T lymphocytes for anti-tumor immunity ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, effectively activated T cells. The study also indicated that lung cancer patients with high mast cell infiltration in the tumor microenvironment exhibited better overall and disease-free survival ( 69 ). In addition, it has been reported that MHC protein is one of the key molecules in presenting antigens and activating T lymphocytes for anti-tumor immunity ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…The number of infiltrating MCs correlated positively with poor cancer prognosis 78 , 79 . Recently, Leveque et al have demonstrated that tumor-associated mast cells (TAMCs), a heterogeneous population, harbor a distinct phenotype compared to MCs present in the non-lesional homologue of lung cancer 80 . It is further noted that the TAMCs subset expressing alpha E integrin, namely CD103+ TAMCs, appeared more actively to interact with CD4+ T cells and located closer to tumor cells than their CD103- counterparts.…”
Section: The Intricate Network Sustaining Immunosuppression In Timementioning
confidence: 99%
“…It is further noted that the TAMCs subset expressing alpha E integrin, namely CD103+ TAMCs, appeared more actively to interact with CD4+ T cells and located closer to tumor cells than their CD103- counterparts. Recruitment of TAMCs was mediated by chemotactic agents released by TME, such as VEGF, CXC chemokine ligand (CXCL)12, PGE2, and platelet-derived growth factor (PDGF) 80 , 81 . Activated TAMCs could express CCL5 and IL-33 to further recruit MCs into tumor sites and activate themselves in an autocrine manner.…”
Section: The Intricate Network Sustaining Immunosuppression In Timementioning
confidence: 99%
See 1 more Smart Citation
“…The specifics of the tumor microenvironment, such as hypoxia, low pH, and metabolite composition, can then imprint the developing and maturing MCs with a tumor microenvironment-specific activation phenotype, whose impact on the tumor could be hardly inferred from plain numbers of infiltrating MCs and their associations with the disease severity. In addition, mast cells in the tumor microenvironment can be phenotypically/functionally heterogeneous [ 58 ]. MCs heterogeneity was initially described based on their localization and protease content.…”
Section: Mcs In Solid Tumorsmentioning
confidence: 99%